2016
DOI: 10.1177/0022146515627850
|View full text |Cite
|
Sign up to set email alerts
|

Religious Attendance and the Mobility Trajectories of Older Mexican Americans

Abstract: Does religious involvement favor physical functioning? At this point, there is no consistent empirical evidence concerning the true nature of the association (Benjamins 2004;Fitchett et al. 2013;Powell, Shahabi, and Thoresen 2003). According to a recent study by Fitchett and colleagues (2013:235), "considerable uncertainty remains about the exact influence of religious beliefs and practices on health outcomes in older adults, such as disability, which is a critical marker of overall physical health in late lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 68 publications
2
14
0
9
Order By: Relevance
“…Although research suggests that social integration, social engagement, and social support are associated with better mental health, physical health, and health-related behavior in various Hispanic groups (Brown et al, 2009; Finch & Vega, 2003; Gallo et al, 2015; Garcia et al, 2013; Hernandez et al, 2005; Hill et al, 2006, In press; Russell & Taylor, 2009; Vega & Kolody, 1985), we could find only one study focusing on social support and mortality risk in the Mexican American population. In their analysis of data from the Corpus Christi Heart Project, Farmer and colleagues (1996) show that Mexican Americans recovering from heart attacks with low levels of social support (based on an index of marital status, living arrangements, and informational support) exhibit a 238% increase in the risk of mortality as compared to their counterparts with moderate and high levels of social support.…”
Section: Theoretical Backgroundmentioning
confidence: 91%
“…Although research suggests that social integration, social engagement, and social support are associated with better mental health, physical health, and health-related behavior in various Hispanic groups (Brown et al, 2009; Finch & Vega, 2003; Gallo et al, 2015; Garcia et al, 2013; Hernandez et al, 2005; Hill et al, 2006, In press; Russell & Taylor, 2009; Vega & Kolody, 1985), we could find only one study focusing on social support and mortality risk in the Mexican American population. In their analysis of data from the Corpus Christi Heart Project, Farmer and colleagues (1996) show that Mexican Americans recovering from heart attacks with low levels of social support (based on an index of marital status, living arrangements, and informational support) exhibit a 238% increase in the risk of mortality as compared to their counterparts with moderate and high levels of social support.…”
Section: Theoretical Backgroundmentioning
confidence: 91%
“…As principais características dos estudos estão incluídas na Tabela 1. Em relação ao tipo de estudo, todos são caracterizados como observacionais, sendo 6 estudos de coorte (Berges, Kuo, Markides, & Ottenbacher, 2007;Hybels, et al, 2012;Cohen-Mansfield, Shmotkin, & Hazan, 2016;Hill, et al, 2016); e 1 estudo transversal (Coleman, et al, 2011).…”
Section: Características Dos Estudosunclassified
“…O período dos estudos variou de 2007 (Berges, Kuo, Markides, & Ottenbacher, 2007); a 2016 (Cohen-Mansfield, Shmotkin, & Hazan, 2016;Hill, et al, 2016), sendo que foram incluídos estudos publicados nos últimos 10 anos.…”
Section: Características Dos Estudosunclassified
See 1 more Smart Citation
“…It assesses five different domains of cognitive function: (1) orientation with a maximum of 10 points, (2) memory with a maximum of 6 points, decline, with a corresponding significant reduction in caregiver burden [15]. This was explained by an increase in social integration, better behavioral self-control [16], and fewer life event stresses among those who are religiously active [17]. Religious involvements have also been associated with lower depression prevalence [18,19], a 14 years follow-up study in Canada demonstrated that more religious involvements reduced risk of developing major depression by 22% [20].…”
Section: Outcome Variablesmentioning
confidence: 99%